PELATIHAN FOTO DAN VIDEO UNTUK PEMASARAN MEDIA SOSIAL IRT JAMU HERBAL KELOMPOK KOLOK DESA BENGKALA - Ni Putu Linda Santiari; I Putu Ramayasa; I Wayan Kayun Suwastika; Sindyawati Rari Duli Goran Tokan; Ni Nyoman Supuwiningsih; I Gede Surya Rahayuda (Jurnal Pengabdian Informatika, 2025)
This community service activity aimed to enhance the digital marketing capacity of home-based herbal drink enterprises operated by the deaf community in Bengkala Village, Buleleng Regency. The main problems faced by the partner were low digital marketing literacy and limited skills in producing attractive visual product content, resulting in reliance on conventional promotion methods and limited market reach. The implementation employed a descriptive-participatory approach, including initial observation, brief interviews, offline training on basic product photography and video recording using smartphones, and online training on the use of Facebook as a digital marketing platform. The results indicated an improvement in the partner’s understanding of social media functions for marketing purposes and basic competencies in product photography and video techniques, such as lighting, shooting angles, and product arrangement. Although consistent promotional content has not yet been produced, the training successfully built initial readiness and awareness of the importance of digital marketing. This activity contributes to strengthening the capacity of home-based enterprises by utilizing local potential and supporting the inclusive values of Bengkala Village.